Benign acute myositis in an adult patient - Chanson, Jean-Baptiste (BMJ Case Rep, 2018)
The benign acute childhood myositis presents as a marked and painful oedema of leg muscles in the days following a viral illness. This disease is often considered as occurring only in children. We report the case of a 32-year-old patient who presented with severe pain and oedema of both legs associated with motor deficit of lower extremities. He suffered from a grippal syndrome for 4 days. Creatine kinase blood level rose up to 39 394 IU/L (n<200) and a muscle biopsy of left tibialis anterior found necrosisand regeneration of myocytes without inflammatory infiltrates. All clinical and paraclinical abnormalities spontaneously disappeared in a few days. This case illustrates that a disorder similar to benign acute childhood myositis may occur in adult patients. Muscle biopsy might be avoided in typical cases because of the favourable evolution.